Traditional Communication as a Tool For Conveying the Identity of Plural Communities - Hendri Ruswandi (Zona Education Indonesia, 2023)
The purpose of this study is to find out how the pattern of communication messages conveyed by each tribe to show that it is their identity. This research uses qualitative methods used to analyze, examine and examine a natural condition of objects. The description is that in this approach the researcher is a key instrument, then this approach is characterized by data collection techniques that can be triangulated (combined). The results of this study show that the process of delivering messages to a plural society can be reviewed from several forms of traditional media, namely oral media, partly oral media, and non-verbal media. The obstacle to the delivery of traditional communication in a pluralistic society is a lack of understanding of nationalist values. On the other hand, another obstacle is the lack of maintaining social identity on the ethnic concept of a group caused by factors of geographical isolation and social isolation